Ish - Reynolds, Peter, 1961- (Cambridge, Mass. : Candlewick Press, 2004)
Ramon loses confidence in his ability to draw, but his sister gives him a new perspective on things.
Keywords: Self-confidence -- Fiction; Drawing -- Fiction; Brothers and sisters -- Fiction